2020
DOI: 10.1097/pas.0000000000001458
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Clinicopathologic Characteristics of PRKAR1A-inactivated Melanomas

Abstract: Melanocytic tumors with inactivation of protein kinase A regulatory subunit-α (PRKAR1A) have large oval nuclei and intense pigmentation. Historically, these tumors have been categorized under various names, including epithelioid blue nevus, pigmented epithelioid melanocytoma (PEM) and animal-type melanoma. Although a subset of PEM harbor BRAF activating mutations and biallelic inactivation of PRKAR1A, there are only a few reports of melanomas, or of tumors with genomic alterations beyond those of PEMs. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…25,26 To the best of our knowledge, this is the first case of BAP1-inactivated melanoma with TERT-p hot spot mutation. A similar stepwise molecular progression to melanoma in pigmented epithelioid melanocytoma 25 and deep penetrating nevus have been proposed. 27 In conclusion, we report a paradigmatic case of BAP1inactivated melanoma supporting a stepwise progression from a nevus to melanoma through a melanocytoma stage (BIMT) from both histological and molecular viewpoints.…”
Section: Discussionmentioning
confidence: 85%
“…25,26 To the best of our knowledge, this is the first case of BAP1-inactivated melanoma with TERT-p hot spot mutation. A similar stepwise molecular progression to melanoma in pigmented epithelioid melanocytoma 25 and deep penetrating nevus have been proposed. 27 In conclusion, we report a paradigmatic case of BAP1inactivated melanoma supporting a stepwise progression from a nevus to melanoma through a melanocytoma stage (BIMT) from both histological and molecular viewpoints.…”
Section: Discussionmentioning
confidence: 85%
“…In 2018, Robledo-Sánchez et al [ 2 ] reported a rare case of ATM in a 79-year-old subject who died a few months later from metastatic dissemination. In particular, in recent years, an increasing amount of immunohistochemical and molecular evidence is trying to elucidate the mechanisms of etiopathogenesis; in detail, in two recent works [ 9 , 21 , 22 , 23 , 24 ], Cohen et al have identified an absence of mutation in the codifying gene for the protein PRKAR1A in molecular terms, but demonstrated a loss of immunohistochemical expression of this marker, proposing a possible diagnostic aid for PEMs with respect to lesions that can mimic them as conventional, cellular, or malignant blue nevus and deep penetrating nevus (DPN). Additionally, a recent study showed the presence of GNAQ mutations in PEMs; thus, these studies provided molecular support for the classification of these tumors as variants or blue nevi [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several melanocytomas arise de novo (without a preexsisting common nevus): for example, cases of "pure" (noncombined) PEM are also genetically peculiar because often they harbor kinase (most commonly PRKA, but also NTRK1 and NTRK3) (38) fusions as the initiating event. Most of these dermal-based tumors are clinically stable; however, they can display various degrees of histopathological atypia (39)(40)(41)(42). Increasing atypical histopathological features may correlate with increased risk of disease progression ( 43), but available data are too weak because of the relative rarity of these tumors and the need of long-term follow-up data.…”
Section: Nevi As Potential Precursors To Melanomamentioning
confidence: 99%
“…Figure 6 illustrates the clinicopathological features of an ulcerated melanocytic malignancy histopathologically composed of large epithelioid cells with Spitz-like features, but immunohstichemically typifi ed as a " classical" melanoma because of its immunohistochemical positivity to the anti-BRAF mutated protein VE1 antibody. Parenthetically, PEM-like (75,76) and DPN-like melanomas (77, 78) might be differentiated from their "melanocytoma counterpart" based on immunohistochemical and/or genetic findings akin to "classical" melanoma.…”
Section: A Management-based Approach: the Mpath-dx System And Beyondmentioning
confidence: 99%